An Improved Entity Similarity Measurement Method - LV Gang; Chen Sheng-bing (Universitas Ahmad Dahlan, 2014)
To facilitate the integration of learning resources categorized under different ontology representations, the techniques of ontology mapping can be applied. Through many algorithms and systems have been proposed for ontology mapping, they do not have an automatic weighting strategy on class features to automate the ontology mapping process. A novel method of computing the feature weights is proposed by feature semantic analysis, defining characteristics of the different entities similarity calculation model and weight calculation model. The results show that it makes the ontology mapping process more automatic while retaining satisfying accuracy. Improve ontology mapping effectiveness.